A Photoaddressable Liquid Crystalline Phase Transition in Graphene Oxide Nanocomposites. (14th April 2019) - Crespo, Maria; Santagiuliana, Giovanni; Picot, Olivier; Portale, Giuseppe; Bilotti, Emiliano; Gautrot, Julien E.
Abstract: The multifunctionality of graphene has the potential to unlock important developments in nanocomposite science. However, the manipulation of graphene without interfering with its unique properties and while controlling its spatial organization remains challenging. Here, the formation of a photoaddressable liquid crystalline (LC) solution through the stabilization of graphene oxide (GO) with photocleavable brushes is described. The LC behavior leads to the thermodynamic entrapment of GO into low aspect ratio domains that fail to display the properties typically predicted for graphene nanocomposites. The morphology and structural and electronic performance of these nanocomposites are regenerated through the brush cleavage, which controls the phase transition of the LC phase. These results show that kinetic control of graphene assembly can be an attractive tool toward the dynamic regulation of processable sol states and structured percolated networks for rational composite manufacturing. Abstract : Photoaddressable liquid crystalline (LC) solutions of graphene oxide (GO) stabilized with photocleavable brushes display phase transition upon UV light irradiation. The resulting change in the steric stabilization of GO platelets results in LC phase release and the establishment of a percolated network, enabling the design of solution‐processable dielectric/conductive composites.